2019
DOI: 10.3390/sports7020052
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Exercise Dependence of Athletes Doing Kickboxing, Taekwondo, and Muay Thai

Abstract: Debates about the conditions in which the frequency and intensity principles of regular exercise, depending on the fact that a sports background can be accepted as extremism, are still a controversial topic. The purpose of this research was to investigate the exercise dependence of athletes who practice Kickboxing, Taekwondo, and Muay Thai. The study included 141 athletes, consisting of 87 men and 54 women. The Exercise Dependence Scale-21 (EDS-21), composed of 21 items developed by Hausenblas and Downs and ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Levit et al (2018) found no difference in the frequency of EA between the sexes. This result is consistent with other studies that found no difference between male and female athletes in the risk of EA (Bingol & Bayansalduz, 2016;De la Vega et al, 2016;Orhan et al, 2019;Reche et al, 2018;Smith et al, 2010;Smith & Hale, 2004;Zeulner et al, 2016). However, two studies reported that female and male athletes might differ in their risk of EA.…”
Section: Correlates Of Ea In Athletessupporting
confidence: 92%
See 3 more Smart Citations
“…Levit et al (2018) found no difference in the frequency of EA between the sexes. This result is consistent with other studies that found no difference between male and female athletes in the risk of EA (Bingol & Bayansalduz, 2016;De la Vega et al, 2016;Orhan et al, 2019;Reche et al, 2018;Smith et al, 2010;Smith & Hale, 2004;Zeulner et al, 2016). However, two studies reported that female and male athletes might differ in their risk of EA.…”
Section: Correlates Of Ea In Athletessupporting
confidence: 92%
“…The included studies examined participants from different sports. Nine of the included studies tested participants from mixed sports (Bingol & Bayansalduz, 2016;De La Vega et al, 2016;McNamara & McCabe, 2012;Müller et al, 2015;Orhan et al, 2019;Reche et al, 2018;Torstveit et al, 2019;Weinstein et al, 2015;Zeulner et al, 2016), three examined runners (Çetin et al, 2020;Smith et al, 2010;Szabo et al, 2013), one looked at elite bodybuilders (Smith & Hale, 2004), one focused on elite dancers (Akehurst & Oliver, 2014), and one examined triathletes (Youngman & Simpson, 2014). Two of the 17 studies did not report information on the type of sports the participants engaged in (Conesa et al, 2017;Levit et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the heart rate at rest and its maximum value as the reaction indicator to competitive load in martial arts is offered [5]. The importance of the cardiovascular system parameters in kickboxing athletes state monitoring is confirmed [6]. Functional tests with the standardized loads estimate the subjects' optimum adaptation opportunities.…”
Section: Introductionmentioning
confidence: 99%